Brokering Empire : Trans-Imperial Subjects between Venice and Istanbul - Rothman, E. Natalie (Ella Natalie), 1976- (Book collections on Project MUSE., 2012)
"Explores how diplomatic interpreters, converts, and commercial brokers mediated and helped define political, linguistic, and religious boundaries between the Venetian and Ottoman empires in the sixteenth and seventeenth centuries."--Author's Web site.